Saving and Spending Habits of Overseas Filipino Workers (OFWs) and Their Families in Region Xi, Philippines - Melba L. Manapol; Sheryl R. Lopez; Ma. Vanessa E. Sobrejuanite (Indonesian Social Work Consortium (ISWC), 2022)
This study on spending and savings pattern of Overseas Filipino Families (OFWs) and their left behind families is an attempt to understand the social and economic context of Filipino migration. Specifically, the study hopes to describe where the hard-earned money of OFWs goes and on whether or not they are able to save. Patterns of spending and saving of their left behind families were also investigated. The study employed a mixed methods research approach particularly survey of 150 respondents composed of 75 OFWs and 75 left behind families. An in-depth interview of 15 left behind families and key informants’ interview of three officials of the Overseas Workers Welfare Administration (OWWA) and Mindanao Migrants Center for Empowerment (MMCEAI) were also conducted to support findings of the survey. Significant findings of the study revealed that the top three spending items of OFWs include remittance to family back home, food and communication. The left behind families, on the other hand, spend the money they receive on education, food, utilities and transportation. The OFWs and their left behind families are able to save and invest. The study also found that some significant correlations exist between and among the following variables such as age, number of years working abroad, type of work, amount saved and amount of remittance. Major recommendations of the study include Financial Literacy and Investment training be given to OFWs and their families. The same trainings should be part of PDOS and Orientation modules given to OFWs and their families.